Regional Bank customer relationship management model through Public Relations functions : (Case study at Regional Development Bank, Special Region of Yogyakarta) - Sri Wahyuningsih, Yuni; Rochayanti, Christina; Lestari, Puji (COMMICAST, 2024)
The banking industry, in practice, was established as the community's economic foundation that provides financial services expected to restore and enhance national and regional economic growth. Bank BPD DIY has a strategic role as a government partner and a motor accelerator of regional development in the Special Region of Yogyakarta. State civil apparatus (ASN) DIY is required to use Bank BPD DIY; it is necessary for customer relationship management (customer). This study aimed to find a model of customer relationship management of regional banks through public relations functions. This research uses a descriptive qualitative approach with a case study method. The results of this study indicate that the customer relationship management model at Bank BPD DIY is carried out through three aspects. The first is to provide excellent service (excellent service), which is implemented by implementing the main values of Bank BPD DIY, namely respect, accuracy, modernity, trust, and reliability (friendly), providing funds and credit services, mobile banking, and customer service, and call center. Second, build customer satisfaction and loyalty through programs that provide promos, giveaways, sweepstakes, birthday greetings, and Corporate Social Responsibility. Third, develop good relationships with consumers through the use of social media such as Facebook, Instagram, Twitter, and WhatsApp broadcasts, organizing events, as well as providing sponsorship assistance in the form of products and cash.